De‐Icer Thaws Water Services. Issue 10 (1st October 2014) - Beck, David
Abstract : The De‐Icer was created by Brookfield Water Utility, Brookfield, Wisconsin, to thaw water services, which had frozen during the winter of 2014. The De‐Icer has reduced repair costs, increased efficiency, and improved safety by eliminating the need to dig up services to thaw them out. In return, the device restores water service to customers. The De‐Icer requires no special tools and is simple to use, benefiting all utilities required to maintain water service in subzero temperatures.